2005
DOI: 10.1197/jamia.m1700
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Health Records on Time Efficiency of Physicians and Nurses: A Systematic Review

Abstract: A systematic review of the literature was performed to examine the impact of electronic health records (EHRs) on documentation time of physicians and nurses and to identify factors that may explain efficiency differences across studies. In total, 23 papers met our inclusion criteria; five were randomized controlled trials, six were posttest control studies, and 12 were one-group pretest-posttest designs. Most studies (58%) collected data using a time and motion methodology in comparison to work sampling (33%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
467
3
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(503 citation statements)
references
References 52 publications
17
467
3
16
Order By: Relevance
“…Based on our small convenience sample of clinicians at these three community hospital sites, it appears that clinicians recognize that during the transition period, many work processes will take longer and that there will be some new work on their part as they become accustomed to the new system. None of our interviewees mentioned that the new system would continue to slow them down after the initial learning period (as we and others [8,19] have found at multiple CPOE implementation sites). In addition, many clinicians were worried about how they would take care of patients if/when the system went down.…”
Section: Discussion Survey Resultsmentioning
confidence: 78%
“…Based on our small convenience sample of clinicians at these three community hospital sites, it appears that clinicians recognize that during the transition period, many work processes will take longer and that there will be some new work on their part as they become accustomed to the new system. None of our interviewees mentioned that the new system would continue to slow them down after the initial learning period (as we and others [8,19] have found at multiple CPOE implementation sites). In addition, many clinicians were worried about how they would take care of patients if/when the system went down.…”
Section: Discussion Survey Resultsmentioning
confidence: 78%
“…25,26 One systematic review found EHR use to be more efficient for documentation by nurses than by physicians, but did not distinguish between types of clinical settings. 10 We found no studies assessing EHR effects on the work of non-clinical staff.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies point to potential EHR-related quality and safety gains due to increased adherence to guideline-based care, 1,2 more complete documentation, 3,4 and fewer medical errors. 5,6 Efficiency gains have been shown to result from electronic ordering 7,8 and from improved access to clinical information, 9,10 which can reduce redundant services. Despite these potential benefits of EHR use, research has also shown variable impact of EHR use on efficiency, and thus on the workload burdens experienced by health care workers.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, one of the "problems with computers" 85 is a failure to account for the accumulated effect of small temporal disruptions on the overall performance of human systems. [85][86][87] Consider the cumulative impact of dealing with pop-up ads on the web, or spending an inordinate amount of time being shuffled from one multilayered telephone answering system to another before being connected to an advice nurse at a hospital. The error is one of myopia, argued Zuboff and Maxmin, 88 as engineers focus solutions on single transactions without considering the impact of multiple interactions on trust and relationships.…”
Section: Safetymentioning
confidence: 99%